Assessment without action; a randomised evaluation of the interRAI home care compared to a national assessment tool on identification of needs and service provision for older people in New Zealand. (3rd May 2013) - Parsons, Matthew; Senior, Hugh; Mei‐Hu Chen, Xenia; Jacobs, Stephen; Parsons, John; Sheridan, Nicolette; Kenealy, Timothy
Abstract Comprehensive geriatric assessment (CGA) is considered the cornerstone of good practice, as it identifies need across multiple domains such as social, physical and psychological. The interRAI home care (interRAI‐HC), probably the most well‐researched and supported community‐based CGA has been implemented globally, often at considerable expense. Policy‐makers, managers and clinicians anticipate significant gains in health outcomes following such investment; however, the implementation of CGA is often undertaken in the absence of community service development. This study sought to compare the interRAI‐HC with an existing CGA [the Support Needs Assessment (SNA)] in community‐dwelling older people. A randomised controlled trial was undertaken from January 2006 to January 2007 comparing the interRAI‐HC and the SNA in 316 people (65+) referred for assessment of needs with follow‐up at 1 and 4 months. Outcomes included health‐related quality of life, physical function, social support, cognitive status, mood and health service usage as well as identified need. The study found that significantly more support needs were identified using the interRAI‐HC compared to the SNA. More social and carer support were recommended by SNA and more rehabilitation and preventive health screens were recommended by interRAI‐HC. Despite these differences, the mean healthcare use was similar at 4 months, although interRAI‐HC participants had more Emergency Department presentations and hospital admissions. No statistically significant differences between groups were reported in terms of outcomes. In conclusion, the interRAI‐HC was found to identify more unmet support needs than the SNA though resulted in no favourable outcomes for the older person or their carer. The study highlights the need to invest attention around the service context to maximise outcomes based on identified needs.